2015
DOI: 10.1111/sjpe.12067
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of a Working Time Regulation on Capital Operating Time: The French 35‐hour Work Week Experience

Abstract: We construct shift-work-based capital operating time indicators. Using differences-in-differences econometric models, we show that the implementation of the 35-hour work week did not induce any reduction in COT. Hence, firms increased shift-work to compensate for the decrease in working hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This implies that there needs to be different policy responses to increased unemployment. Similar evidence concerning sectors impacted by the pandemic reported that the largest employment losses were in the leisure and hospitality sectors, in addition to other services, including trade, transportation, and utility services, and in general, sectors which were less able to make use of teleworking (Gilles 2015). The sectoral differences in crisis severity may also produce a widening gender gap, given the incidence of female employment in the most affected sectors (Gilles and L'Horty 2003).…”
Section: Pandemic Measures and Their Economic Impactmentioning
confidence: 82%
See 1 more Smart Citation
“…This implies that there needs to be different policy responses to increased unemployment. Similar evidence concerning sectors impacted by the pandemic reported that the largest employment losses were in the leisure and hospitality sectors, in addition to other services, including trade, transportation, and utility services, and in general, sectors which were less able to make use of teleworking (Gilles 2015). The sectoral differences in crisis severity may also produce a widening gender gap, given the incidence of female employment in the most affected sectors (Gilles and L'Horty 2003).…”
Section: Pandemic Measures and Their Economic Impactmentioning
confidence: 82%
“…Longterm employment losses arose, caused by firms' definitive closures and difficulties in re-entering the labor market for many workers (Foss 1963). More losses are expected in low-wage and retail sectors, which is in contrast with the previous recession, where greater difficulties arose for the high-wage, construction, and manufacturing sectors (Gilles 2015). This implies that there needs to be different policy responses to increased unemployment.…”
Section: Pandemic Measures and Their Economic Impactmentioning
confidence: 95%